Design a Parallel Pipeline Radix-4 FFT Architecture - Roopak Kumar Verma, Amaresh Kumar, Dr. Manish Mishra , (International Journal of Scientific Research and Management (IJSRM), 2014)
This paper presents a novel design to develop parallel pipelined architectures for the fast Fouriertransform (FFT). The architecture is based on the radix-4 algorithm. By exploiting the regularity of thealgorithm, butterfly operation and multiplier modules were designed. The architecture adopts fourbutterflies, and the pipeline stage is optimized to balance the processing speed and the area. Novel parallelpipelined architectures for the computation of complex and real valued fast Fourier transform are derived